Potential use of nir and visible spectroscopy to analyze chemical properties of thermally treated wood - Cristina Lengowski, Elaine; Inês Bolzon de Muñiz, Graciela; Klock, Umberto; Nisgoski, Silvana (Maderas. Ciencia y Tecnología, 2018)
The modification of wood by thermal treatments produces characteristic changes in its chemical composition and surface color and can improve the structural and esthetic quality. The objective of this paper is to evaluate the potential of near infrared and visible spectroscopy to predict the modifications in chemical composition of Eucalyptys grandis and Pinus taeda after thermal treatment. Near infrared and visible spectra were collected directly on the longitudinal surface of wood samples. The thermally modified wood of both species showed higher content of lignin and extractives than the untreated wood. There was darkening of thermally modified wood, as a result of chemical modification caused by heat. The Near infrared/visible technique identified the groups that were modified by treatment. NIR and visible spectroscopy can be used to predict chemical composition of natural or thermally treated Eucalyptus grandis and Pinus taeda.